The Role of Civil Defense in the Republic of Serbia’s Crisis Management System - Milica Mladenovic; Nenad Komazec; Sinisa Domazet (Journal of Liberty and International Affairs)
This paper examines the role of civil defense in Serbia’s crisis management system, focusing on its contribution to prevention, preparation, response, and recovery phases. The study addresses the insufficient integration of civil defense at the national level and identifies its key functions and opportunities for improvement. Using literature analysis, legal frameworks, good practices, and expert surveys, the research highlights the need for a clear normative definition of civil defense's role within the system. It emphasizes the practical establishment and development of the system for effective crisis response. The conclusion underlines the importance of a proactive approach and strengthening community resilience by fully integrating civil defense into Serbia’s crisis management framework.